ANALISIS AYAT JIHAD SURAT AL-BAQARAH: 190-192 DALAM PERSPEKTIF TAFSIR AL-JAMI' LI AHKAM AL-QUR'AN KARYA IMAM AL-QURTUBI - Ahmad Jamil; Khoirun Nidhom (LPPM Institut Daarul Qur'an Jakarta, Indonesia, 2025)
The concept of jihad has often sparked controversy, particularly when narrowly interpreted as religious justification for violence. In today's global context, jihad is frequently misunderstood and exploited by extremist groups to legitimize radical actions. This study aims to analyze the interpretation of jihad in Surah Al-Baqarah verses 190–192 based on the perspective of Imam Al-Qurtubi through his seminal work Al-Jami’ li Ahkam al-Qur’an. This research employs a qualitative-descriptive method using a library research approach. The findings reveal that Al-Qurtubi interprets jihad as a defensive effort against oppression and aggression, to be carried out justly, proportionally, and within the ethical boundaries of Islamic law. Warfare is prohibited in the Sacred Mosque (Masjid al-Haram) unless provoked, and hostility must cease when the aggressor withdraws. These interpretations underscore that jihad, in Al-Qurtubi’s view, is not an expansionist doctrine of violence but a pursuit of justice and peace. The relevance of this interpretation is significant in the modern era as it helps rectify misconceptions surrounding jihad and contributes to a narrative of Islam that upholds peace and human dignity. This study is significant for its contribution to strengthening the discourse of religious moderation through a contextual and contemporary reading of classical Islamic exegesis